Pretreatment of Arundo donax L. for photo-fermentative biohydrogen production by ultrasonication and ionic liquid. (June 2023) - Zhang, Quanguo; Yang, Jiabin; Zhang, Tian; Shui, Xuenan; Zhang, Huan; Chen, Zhou; He, Xun; Lei, Tingzhou; Jiang, Danping; Elgorban, Abdallah M.; Syed, Asad; Kumar Solanki, Manoj
Graphical abstract: Highlights: Combined ultrasonic and ionic liquid pretreatment was applied to PFHP. Delignification of biomass and hydrogen yield were positive correlated. Pretreatment temperature had the strongest linear correlation with HY. Combined energy production approaches might be useful for improved ECE. Abstract: Combined pretreatment methods were assumed to further enhance photo-fermentative biohydrogen production (PFHP) from lignocellulosic biomass. For this purpose, an ultrasonication assisted ionic liquid pretreatment was applied to Arundo donax L. biomass for PFHP. The optimal condition for the combined pretreatment was 16 g/L of 1-Butyl-3-methylimidazolium Hydrogen Sulfate ([Bmim]HSO4 ) combined with ultrasonication at a solid to liquid ratio (SLR) of 1:10 for 1.5 h under 60 °C. Under this condition, the maximum delignification of 22.9 % was obtained, in addition, the hydrogen yield (HY) and energy conversion efficiency (ECE) were enhanced by 1.5-fold and 46.4 % ( p  < 0.05) compared to untreated biomass, respectively. Moreover, heat map analysis was performed to evaluate the correlation between pretreatment conditions and corresponding results, suggesting pretreatment temperature had the strongest (absolute value of Pearson's r was 0.97) linear correlation with HY. Combined multiple energy production approaches might be useful for further improved ECE.